(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Bhagandara (Fistula in ano) described by Aacharya Sushruta can be categorized under Dushta Vrana i.e., noncollapsable, unhealthy infected tunnelling wound with persistent drainage of pus. According to Sushruta treatment given for Bhagandara is Chedana Karma (excision of tract i.e., Fistulectomy) along with Ksharsutra Chikitsa. But as the surgical techniques are opted in infected stage of wound it may lead to complications like recurrence, infection and incontinence. Ksharsutra (medicated seton) is a device to deliver medicine to the non- approachable wound surface causes Shodhana (Purification) and Ropana (Healing) of fistulous tract simultaneously. But, time duration required for this treatment is slightly longer as compared to Fistulectomy. Methodology: The study was an open clinical trial done on five patients, clinically diagnosed as a case of low anal fistula. The aim was to minimise the duration of treatment and to evaluate the pattern and duration of healing of post fistulectomy surgical wound if it performed after achieving Shuddhavastha by Ksharsutra. Study group were treated with Ksharsutra ligation under local anaesthesia and as Shuddhavastha was achieved Fistulectomy was done under spinal anaesthesia. Result: After Ksharsutra ligation Shuddha Vranalakshana was achieved on third or fourth sitting, whereas the Unit Healing Rate observed after fistulectomy was 0.15 sq.cm/day. No recurrence was noted in any of the 5 patients. Conclusion: Combine therapy of Ksharsutra ligation followed by Fistulectomy curtail the prolong duration of treatment which is quite longer in Ksharsutra therapy. It also shows significant results in recurrence as surgical procedure is opted in Shuddhavastha of Vrana.